2016
DOI: 10.1002/jsfa.7642
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic fractionation and molecular mass characterization of Cercidium praecox (Brea) gum

Abstract: The findings showed that BG consists of several fractions with heterogeneous chemical composition and polydisperse molecular weight distributions. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…1 A), the first peak (labeled peak 1) appeared at elution volume of 34 mL and the second (peak 2) at 46 mL, being similar to the earlier reported profile (Castel et al, 2016). The reported molecular mass of peaks 1 and 2 were 1.92 × 10 5 and 2.79 × 10 3 kDa, respectively (Castel et al, 2016). On the other hand, RI profiles of BG thermally treated samples (BGTT) showed no great variation regarding untreated BG profile, however, a small increase in the height of the peaks was observed by increasing treatment time.…”
Section: Molecular Mass Distributionsupporting
confidence: 88%
See 2 more Smart Citations
“…1 A), the first peak (labeled peak 1) appeared at elution volume of 34 mL and the second (peak 2) at 46 mL, being similar to the earlier reported profile (Castel et al, 2016). The reported molecular mass of peaks 1 and 2 were 1.92 × 10 5 and 2.79 × 10 3 kDa, respectively (Castel et al, 2016). On the other hand, RI profiles of BG thermally treated samples (BGTT) showed no great variation regarding untreated BG profile, however, a small increase in the height of the peaks was observed by increasing treatment time.…”
Section: Molecular Mass Distributionsupporting
confidence: 88%
“…BG elution profile monitored by RI showed two peaks (Fig. 1 A), the first peak (labeled peak 1) appeared at elution volume of 34 mL and the second (peak 2) at 46 mL, being similar to the earlier reported profile (Castel et al, 2016). The reported molecular mass of peaks 1 and 2 were 1.92 × 10 5 and 2.79 × 10 3 kDa, respectively (Castel et al, 2016).…”
Section: Molecular Mass Distributionsupporting
confidence: 84%
See 1 more Smart Citation
“…This could be attributed to the complex macromolecular structure of the BG, characterized by a heterogeneous chemical composition system with a broad molecular weight distribution. According to Castel et al (2016), the gum is formed by three different fractions: the bulk of the gum (approx. 84% of the polysaccharides) is a polysaccharide of 2.79 Â 10 3 g/mol; the second major fraction (approx.…”
Section: Droplet Size and Zeta Potential Measurementsmentioning
confidence: 99%
“…Brea gum (BG) is the exudate obtained from the Brea tree (Cercidium praecox). Cerezo et al (1969) and Castel et al (2016) described the chemical structure of BG as an acid heteropolysaccharide that also contains between 4% and 10% of proteins that form a polysaccharide-protein complex. The toxicological analyses of BG indicated that it is not toxic for human ingestion (VON MÜLLER et al, 2009) and it was recently included as a food additive in the Argentine Food Code (ARGENTINA, 2014).…”
Section: Introductionmentioning
confidence: 99%